Cycles of instability: Proximal and distal influences on residential instability among people with histories of homelessness in three Canadian cities. Issue 8 (23rd March 2022) - Czechowski, Konrad; Sylvestre, John; Gogosis, Evie; Agha, Ayda; Kerman, Nick; Polillo, Alexia; Palepu, Anita; Hwang, Stephen W.
Abstract: People with histories of homelessness often have difficulties obtaining and maintaining adequate housing. This qualitative study examined the residential transitions of people with histories of residential instability and homelessness to understand factors contributing to the instability they experience. Interviews were conducted with 64 participants about their housing transitions, in the final year of a 4‐year, prospective cohort study in three Canadian cities (Ottawa, Toronto, and Vancouver). Findings showed that participants pointed to both distal and proximal factors as affecting residential transitions, including interpersonal conflict, safety concerns, substance use, poverty, pests, and health. Many reported disconnection from their housing and a lack of improvement from one housing situation to the next, demonstrating how even when housed, instability persisted. Our study highlights the complexity associated with participants' often unplanned and abrupt residential transitions. The complex and distal issues that affect housing transitions require structural changes, in addition to individual‐based interventions focused on the proximal problems.